Perceptions of Distance Education Students on How a University Education will Help Achieve their Career Goals - Sarah Zipf; Ramazan Gungor (Adult Education Research Conference, 2016)
Using the responses to an open-ended question on the annual web-based scholarship application on how students are planning to use their education in achieving their career goals, this study explored the intersection of educational and career goals of mostly non-traditional students.
Keywords: Higher education; adult students; career goals.